2000
DOI: 10.2355/isijinternational.40.1260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclusion Size on the Nucleation of Acicular Ferrite in Welds.

Abstract: Low-carbon steel weld with a high density of oxide inclusions prepared using a experimental metal-cored wire has been examined to study the effect of inclusion size on the formation of acicular ferrite, and to understand the role of inclusion in the nucleation of ferrite lath. Depending on the ferrite morphology associated with inclusions, a total of 282 inclusions observed under TEM could be classified into two groups, i.e. the non-nucleant and the nucleant. Experimental results showed that the group of inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 20 publications
4
142
1
3
Order By: Relevance
“…The upper size limit for 99 pct of inclusions is marked with a cross for each case. In the literature, several authors [33][34][35][36] described a boost in nucleation potential with the increasing inclusion size, which is in good accordance with earlier findings of Ricks et al [37,38] However, it should be noted that in many cases also, a lower and an upper critical sizes for active inclusions are defined. The lower critical value is the minimum size beneath which particles are too small to act as active nuclei.…”
Section: A Acicular Ferrite Amountsupporting
confidence: 78%
See 2 more Smart Citations
“…The upper size limit for 99 pct of inclusions is marked with a cross for each case. In the literature, several authors [33][34][35][36] described a boost in nucleation potential with the increasing inclusion size, which is in good accordance with earlier findings of Ricks et al [37,38] However, it should be noted that in many cases also, a lower and an upper critical sizes for active inclusions are defined. The lower critical value is the minimum size beneath which particles are too small to act as active nuclei.…”
Section: A Acicular Ferrite Amountsupporting
confidence: 78%
“…Above 1 lm, the probability curve flattens out. Huang et al [34,39,40] who considered inclusions up to 7 lm, observed 1.5 lm as the upper critical value but described a sharp decrease in the nucleation probability above 4 lm, resulting in inert behavior of inclusions larger than 6.5 lm. Similar results were gained by Song et al [41] and Wang et al [42] who found inclusions with sizes ranging from 1 to 3 lm and 1 to 2 lm, respectively, as the most appropriate nuclei.…”
Section: A Acicular Ferrite Amountmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular example appeared in the heat-affected zone of a weldment in a steel that had been "salted" with oxide particles. 38) These particles are intended to maintain fine grain size in the heat-affected zone by providing a dense array of ferrite nucleation sites for retransformation of the austenite in the HAZ.…”
Section: Acicular Ferrite Nucleation From An Oxidementioning
confidence: 99%
“…This is because the microstructure is influenced not only by the particle size, but also by the particle surface composition consisting of nucleation sites such as in the Tirich phase. It has been reported [18][19][20][21][22][23] with respect to the inclusion size that a certain minimum inclusion size is required for intragranular ferrite nucleation and that inclusions smaller than this size are not effective as nucleation sites.…”
Section: Oxide Compositionmentioning
confidence: 99%